Midhaan Dheedhii Omishtumma dabaluu fi Sirna Nyaataa Fooyyessuuf - International Livestock Research Institute (International Livestock Research Institute, 2023)
Monocropping is a long-lasting problem in Bale and Arsi Zones of Ethiopia. This problem results in weed infestation and a wide prevalence of diseases which in turn result in increased production costs and decreased productivity. This video highlights the work of Africa RISING in collaboration with ICARDA to support the smallholder farmers scaling up improved faba bean variety with (high-yielding, disease-tolerant and better market demand seeds) and capacitating farmers, and extension agents to increase availability and accessibility of quality seeds that ensured sustainability.